Estudo da influência no reativo do barramento de um sistema elétrico utilizando cargas eletrônicas em projetos de eficiência energética - Beuter, Carlos Henrique (2015)
Electricity consumption is growing and thoroughly discussed in the national and international literature. As natural resources are limited, associated with environmental barriers for power generation, it is expected a growing concern and quest for power and energy efficiency. However, there was profusion and developments in the technology of electronic equipment, mass-produced in various sectors of activity, whether residential, commercial or industrial. The widespread use of power electronics, microelectronics and microprocessors in all types of equipment, from digital watches to complex automated industrial lines is due in part by the high performance and power efficiency they provide. With this significant increase in electronic loads in the consumer units operating, often in the presence of electric motors, among other charges predominantly inductive, there is the need for an analysis of its possible impact on the energy context. The behavior of linear and non-linear electronic loads can influence the reactive behavior in an electrical system bus. In order to promote discussion and generate knowledge on the subject, the objective of this study is to analyze the behavior of electronic loads, specifically CFLs and tubes with electronic ballasts, in order to compensate the reactive power excess of an inductive load, and watching his possible impact on energy efficiency projects. In the laboratory measurements of compact fluorescent lamps as well as externally, in the field, in bus composed of tubular fluorescent lamps with electronic ballasts, there was a capacitive reactive power flow toward the power supply, in other words, when connected loads electronic alongside a bank of inducing the power factor was offset by reactive lamps. The results obtained in the field and in the laboratory have been validated through a simulation model using the ATP software, at ATPDraw graphical interface, which were modeled a set of compact fluorescent lamps and inductive loads. We analyzed whether this capacitive reactive flow generated by electronic loads can be beneficial or detrimental to the charging system, depending on the time of day that this electronic charge is triggered. In the adopted procedures was concluded that occurs reactive power injection on the bus, helping to improve the power factor of the consumer unit and consequently influencing the reactive power surplus calculation